Event Related Oscillations in Euthymic Patients With Bipolar Disorder - Özerdem, Ayşegül; Kocaaslan, Sibel; Tunca, Zeliha; BAŞAR, EROL (ELSEVIER IRELAND LTD, ELSEVIER HOUSE, BROOKVALE PLAZA, EAST PARK SHANNON, CO, CLARE, 00000, IRELAND, 2008)
Bipolar disorder involves dysfunction in gamma amino butyric acid (GABA)/glutamatergic systems and neural circuits that regulate cognitive processing. Valproate, a mood stabilizing anticonvulsant, modulates GABA/glutamate and shows neuroprotective effect. Electroencephalographic oscillatory activity assessment is an alternative brain imaging technique with high time resolution. It presents integrative brain functioning. We aimed to assess the oscillatory responses of patients with bipolar disorder in euthymic state of bipolar disorder and the changes after treatment with valproate. Event related potentials to visual odd-ball paradigm in 10 euthymic medication free, bipolar patients were measured before and after 6 weeks of valproate monotherapy and compared with sex- and age-matched healthy controls. Delta frequency bands, as representative of signal detection and decision-making, were obtained by digital filtering. At baseline, patients showed higher delta responses to target stimuli in all but significantly left frontal channels in comparison to controls. After 6 weeks of treatment, delta responses decreased significantly in central frontal (Fz) (p: 0.028), left frontal (F3) (p: 0.028), left (T3) (p: 0.015), right anterior (T4) (p: 0.011), and left posterior temporal (T5) (p: 0.011) channels compared to baseline and became no different to the controls, which did not differ between two assessments. The findings point to a diffuse increase in low frequency electrical activity which was prominent in the left frontal location in euthymic patients with bipolar disorder. Reduction of the electrical activity of the left frontal and bilateral anterior temporal areas with treatment may be through modulation of glutamatergic and GABAergic mechanisms and indicative of valproate's neuroprotective effect. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bipolar Disorder; Event Related Oscillations; Delta Responses; Neurocognitive Functioning; Valproate; GABA/glutamate; Neuroprotection; Mood Disorders; Cognitive-Processes; Schizophrenia; Dysfunction; Valproate; Delta; Gamma; Theta; Potentials; Expression; Bipolar Bozukluk; Olaya İlişkin Salınımlar; Delta Yanıtları; Bilişsel İşleyişi; Valproat; Nöro; Duygudurum Bozuklukları; Bilişsel Süreçler; Şizofreni; Fonksiyon Bozukluğu; Delta; Gama; Teta; Potansiyeller; İfade